Correlation of reactivity with structural factors in a series of Fe(II) substituted cobalt ferrites - Sileo, E. E.; Rodenas, L. G.; Paiva-Santos, C. O.; Stephens, P. W.; Morando, P. J.; Blesa, M. A. (Elsevier B.V., 2006)
A series of powdered cobalt ferrites, CoxFe3-xO4 with 0.66 <= x< 1.00 containing different amounts of Fe-II, were synthesized by a mild procedure, and their Fe and Co site occupancies and structural characteristics were explored using X-ray anomalous scattering and the Rietveld refinement method. The dissolution kinetics, measured in 0.1 M oxalic acid aqueous solution at 70 degrees C, indicate in all cases the operation of a contracting volume rate law. The specific rates increased with the Fell content following approximately a second-order polynomial expression. This result suggests that the transfer of Fe-III controls the dissolution rate, and that the leaching of a first layer of ions Co-II and Fe-II leaves exposed a surface enriched in slower dissolving octahedral Fe-III ions. Within this model, inner vicinal lattice Fe-II accelerates the rate of Fe-III transfer via internal electron hopping. A chain mechanism, involving successive electron transfers, fits the data very well. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cobalt ferrites; X-ray anomalous scattering; Rietveld method; kinetic dissolution; electron hopping